Enemy activity as of May 5, 1943. (1943)
Enemy activity for the German 210th Infantry Division. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, 210th Infantry Division Ia, Anlage 3 to KTB, , folder 37889/5, first frame 000140. Translated by Major James F. Gebhardt, USA (retired).